Faktor–Faktor yang Mempengaruhi Perilaku Konsumen Memilih Mobil Bekas Merk Toyota Menggunakan Analisis Faktor - Cindy Febrianita; Minora Longgom; Nonong Amalita (UNIVERSITAS NEGERI PADANG, 2019)
Abstract –There are four factors that influence someone or consumer to choose a product: culture factor, social factor, individual factor, and psychology factor. Many factors that influence someone to choose and its have correlation one with another, so we can processed the data using factor analysis. The results of this research indicate that the factors that affect consument choose to buy secound car brand Toyota there are some factors, the factor is recommendation to choose the product, life style, perception to choose the product, motivation to choose the product, parent existence, and job. Keywords: factors of consumer behavior, secound car brand Toyota, factor analysis